The house across the lake : [large type] a novel - Sager, Riley (Thorndike Press, a part of Gale, a Cengage Company, 2022)
"Casey Fletcher has retreated to the peace and quiet of her family's lake house in Vermont. She passes the time watching Tom and Katherine Royce, the couple living in the house across the lake. One day on the lake, Casey saves Katherine from drowning, and the two strike up a friendship. But the more they get to know each other--and the longer Casey watches--it becomes clear that Katherine and Tom's marriage isn't as perfect as it appears. When Katherine suddenly vanishes, Casey immediately suspects Tom of foul play. What she doesn't realize is that there's more to the story than meets the eye--and that shocking secrets can lurk beneath the most placid of surfaces"--